Application of Trend Analysis on Drought Indices in the West Black Sea Region - Turgay Partal; Ercan Yavuz (Doğal Afetler ve Çevre Dergisi)
This study has been carried out to trend analysis on drought indices in the West Black Sea Region. Drought is very important subject for climate researchers in recent years. In this study, it was investigated whether there is a trend in drought indices by using trend analysis methods. Firstly, the standardized precipitation index and De Martonne index were obtained for the trend analysis. After then, the Mann-Kendall test was applied to the drought indexes. The data network used in this study consists of 6 stations spanning from 1960 to 2015. The used data was selected to reflect general hydro-climatic conditions of the Western Black Sea Region. According to the trend analysis, there is an increasing trend that is not statistically significant at the 5% significance level in all stations in the extremely severe drought class for the 1-month standard precipitation index. On the other hand, the negative z values were determined in annual and winter De-Martonne indexes. The application of a trend detection in observed precipitations were resulted in the identification of decreasing trends in November, December and January precipitations for the mostly of stations.